Antimicrobial therapeutics reviews : antibiotics that target the ribosome - Bush, Karen (Annals of the New York Academy of Sciences, 2011)
"This second installment of Antimicrobial Therapeutics Reviews presents scholarly reviews on several key areas in the field of antimicrobial therapeutics, including several papers on issues relating to antibiotics that target the ribosome. Topics covered include plasmid-encoded resistance determinants for agents that bind the ribosome, new compound classes targeting the ribosome, sequence-specific action of antibiotics binding the ribosome, smFRET approaches to determine MOA of antibiotics binding to the ribosome, new approaches for treating Staphylococcus biofilm infections, and the history of tetracyclins. The volume also features reviews dealing with drug development, such as pleuromutilin discovery and development challenges and an update on newer oxazolidinones such as torezolid and radezolid, and a review on regulatory hurdles for new antibiotics"--Publisher's description